Properties and excitation of solitary perturbations by electron beam in accelerator - Lapshin, V.I.; Maslov, V.I.; Onishchenko, I.N.; Stomin, V.L. (Вопросы атомной науки и техники, 2001)
The excitation of a solitary wave perturbation of electric potential hump type with a large amplitude of an electron beam at the accelerator has been considered. Its properties and dependencies of properties on the amplitude have been investigated. This perturbation propagates in the rest frame of the beam with a velocity, approximately equal to the thermal velocity of beam electrons. The perturbation forms hole and vortex in the electron phase space. The solitary perturbation is excited due to nonlocal interaction of the beam with a metallic wall of final conductivity. This hump of electric potential is the BGK perturbation.